A Markov Chain Analysis on the Impact of German Tax Loss Offset Restrictions1. Issue 1 (8th April 2013) - Cui, Lina
<x xml:space="preserve">Abstract</x> This article presents a set of microsimulation models to derive individual companies' tax data from their time series financial microdata by applying different tax offset restrictions. Based on this model, we develop a Markov chain model for simulating 1828 non‐financial German companies in the Amadeus database to assess the impact of major reforms on German tax offset restrictions since 2001. Main results suggest that: (i) our developed Markov model is able to rather accurately predict the probabilities of a company's taxable profits (losses) in different levels; (ii) the introduction of more strict offsetting rules provides incentive for companies to provide less losses and become more conservative in their business operations; and (iii) the reforms have particularly important impacts on large and very large enterprises and on some sectors such as electricity, gas and water supply, construction and whole sale and retail trade.